Histone Deacetylase Inhibitors as Therapeutic Interventions on Cervical Cancer Induced by Human Papillomavirus - Lourenço de Freitas, Natália; Deberaldini, Maria Gabriela; Gomes, Diana; Pavan, Aline Renata; Sousa, Ângela; Dos Santos, Jean Leandro; Soares, Christiane P. (Frontiers in Cell and Developmental Biology, 2021)
The role epigenetic modifications on carcinogenesis process have received a lot of attention in the last years. Among those , the histones acetylation is a process regulated by histone deacetylases (HDAC) and histone acetyltransferases (HAT), and it plays an important role in epigenetic regulation, allowing the control of the gene expression. HDAC inhibitors (HDACi) induce cancer cell cycle arrest, differentiation and cell death, and reduce angiogenesis and other cellular events. Human papillomaviruses (HPVs) are small, nonenveloped double-stranded DNA viruses. They are major human carcinogens, being intricately linked to the development of cancer in 4.5% of the patients diagnosed with cancer worldwide. Long-term infection of high-risk (HR) HPVs types, mainly HPV16 and HPV18, is one of the major risk factor responsible to promote cervical cancer development. In vitro and in vivo assays have demonstrated that HDACi could be a promising therapy to HPV-related cervical cancer. Regardless of some controversial studies, the therapy with HDACi could target several cellular targets which HR-HPV oncoproteins could be able to deregulate. This review article describes the role of HDACi as a possible intervention in the cervical cancer treatment induced by HPV, highlighting the main advances reached up in the last years and providing insights for further investigations regarding those agents against cervical cancer.